(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article presents the analysis of the improving the quality of education program, developed in one of the central schools of the city from the point of a psychological aspect. There is made a brief overview of the current scientific sources about the lack of psychological literacy of the educational recipients and teachers and the inability to put the existing knowledge into practice. The basic psychological components of the program are investigated in this way: the formation of scientific virtue, the organization of personality-oriented training, the creation of a student’s and teacher’s portfolio as a motivator of activity, the construction of an individual educational trajectory of an educational recipient. Prospects for further exploration in the process of cooperation between higher and secondary schools are outlined.